The influence of product liability on vertical product differentiation - Florian Baumann; Tim Friehe; Alexander Rasch (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper explores the impact of product liability on vertical product differentiation when product safety is perfectly observable. In a two-stage competition, duopolistic firms are subject to strict liability and segment the market such that a low-safety product is marketed at a low price to consumers with relatively small harm levels whereas the safer product is sold at a high price to consumers with high levels of harm. Firms' expected liability payments are critically influenced by how the market is segmented, creating a complex relationship between product liability and product differentiation. We vary the liability system's allocation of losses between firms and consumers. Shifting more losses to firms increases the safety levels of both products, but decreases the degree of product differentiation. Some shifting of losses is always socially beneficial, but the optimum may require that some compensable losses stay with the consumers.
Keywords: D43; K13; L13; 330; product liability; accident; harm; imperfect competition; product safety; vertical product differentiation